Kemampuan komunikasi matematis mahasiswa berdasarkan gender dan gaya kognitif - Santosa, Farah Heniati; Kurniawati, Kiki Riska Ayu; Bahri, Samsul (Jurnal of Math Tadris, 2023)
Abstract This study aims to analyze and describe students' mathematical communication skills based on gender and cognitive style. Researchers involved 97 students at one of the tertiary institutions in the city of Mataram. The instruments used consisted of a test of mathematical communication skills in the form of an essay consisting of 4 questions and a Group Embedded Figure Test (GEFT) to identify students' cognitive styles. Data analysis used two-way ANOVA. The results showed that the mathematical communication skills of female students outperformed the abilities of male students. Regular and thorough characteristics as well as better verbal skills support female students in conveying back mathematical concepts in solving problems. Differences in cognitive styles provide different mathematical communication abilities to students. Students who have a field independent cognitive style have better mathematical communication skills compared to students who have a field dependent cognitive style. Different characteristics in managing information and identifying it are aspects of cognitive style. The results of this study are expected to be one of the references in considering the internal factors that influence mathematical abilities, especially mathematical communication skills.